Structural monitoring and damage identification on a masonry chimney by a spectral-based identification technique - Masciotta, M. G. (2014)
The present work deals with the damage identification of a historical masonry chimney located in Guimarães (Portugal), including a detailed survey, inspection and diagnosis. The chimney was object of a continuous monitoring campaign carried out to catch the evolution of the modal parameters and evaluate the success of the rehabilitation works planned after a lightning accident. Based on the dynamic features extracted from the OMA data, a damage identification analysis was performed making use of different damage identification techniques. Considering the explicit dependence of output-only power spectral densities on frequency contents, a spectral-based identification method was used to detect the damage. Finally, an appropriate localization index was defined combining evolutionary complex eigenvectors obtained from the decomposition of the power spectral density matrix. The results allow to conclude that the spectral-based dynamic identification method is a non-destructive tool able to capture the global behavior of a structure and may reveal itself of great help for exploring damage at an early stage in historical constructions.